Agonist binding to peptide hormone receptors. (1st February 2003) - Wheatley, M.; Hawtin, S.R.; Wesley, V.J.; Howard, H.C.; Simms, J.; Miles, A.; McEwan, K.; Parslow, R.A.
Abstract : A fundamental issue in molecular pharmacology is to define how agonist–receptor interaction differs from that of antagonist–receptor interaction. The V1a vasopressin receptor (V1a R) is a member of a family of related G-protein-coupled receptors (GPCRs) that are activated by vasopressin, oxytocin (OT) and related peptides. A segment of the N-terminus that was required for agonist binding, but not antagonist binding, was identified by characterizing truncated V1a R constructs. Site-directed mutagenesis revealed that a single residue (Arg 46 ) was critical for agonist binding and receptor activation. The N-terminus of the related OT receptor (OTR) could recover agonist binding in a chimaeric OTR N –V1a R construct. Furthermore, Arg 34 of the human OTR, which corresponds to Arg 46 of the rat V1a R, provided agonist-specific binding epitopes in the OTR, indicating a conserved function of this locus throughout this GPCR subfamily. Mutation of Arg 46 revealed that high-affinity agonist binding had an absolute requirement for arginine at this position.